Kernel of Internet of Things:Internet of Data - Qi ZHANG; Hao YANG; Q.S.Quek Tony; Shi JIN; Hong-bo ZHU (物联网学报)
The Internet of Things (IoT) is a collection of devices,sensors and computing capabilities that enable intelligent command and control across vast regions in an automated manner,where data is generated by large-scaled devices and often sent to a centralized system for processing.Therefore,for IoT scenarios,it is important to have an efficient way to collect data at low power,transmit them in very short time,process them in close to real time,and send back the results of this processing.The main data problems in IoT are investigated,and the data entities are organized to form a network,coined as the Internet of Data (IoD),which has huge potential in data-intensive applications.To better understand IoD,the basic concept and main challenges of IoD are also stated.Meanwhile,to provide more detailed understanding,some feasible techniques that can be used in IoD are also explored,like big data,data mining and artificial intelligence,which are all hot research areas and have been studied extensively in recent years.